Violencia intrafamiliar y su influencia en las relaciones interpersonales de un estudiante del Colegio Emigdio Esparza Moreno - Santos Criollo, Karla Elizabeth (2020)
In this present study, the investigation of intrafamily violence, its incidence in the interpersonal relationships of a student, was carried out. It was found that intrafamily violence is an issue that has left unpleasant traces in the lives of many people, having its origin in the family system, it is characterized by exercising control over a person or situation. In this study, a psychotherapeutic intervention was proposed with a cognitive-behavioral approach, in order to reestablish their thought processes or patterns that are interfering in their behavior, through this approach, and with the help of tests, in each of During the sessions, it was possible to detect that the student is a victim of domestic violence, therefore, to a large extent their interpersonal relationships are being influenced by this situation. With different techniques, it was possible to address the current situation that the patient lives, interfering in their thought processes and emotional state, with the aim of improving mental health and that this is reflected in their interpersonal relationships.